Quantification of tumor vessels in glioblastoma patients using time-of-flight angiography at 7 Tesla: a feasibility study - Radbruch, Alexander; Eidel, Oliver; Paech, Daniel; Burth, Sina; Vollmuth, Philipp; Nowosielski, Martha; Bäumer, Philipp; Wick, Wolfgang; Bendszus, Martin; Heiland, Sabine (PLOS ONE, 2014)
Purpose: To analyze if tumor vessels can be visualized, segmented and quantified in glioblastoma patients with time of flight (ToF) angiography at 7 Tesla and multiscale vessel enhancement filtering. Materials and Methods: Twelve patients with newly diagnosed glioblastoma were examined with ToF angiography (TR515 ms, TE54.8 ms, flip angle515˚, FOV51606210 mm2, voxel size: 0.3160.3160.40 mm3) on a whole-body 7 T MR system. A volume of interest (VOI) was placed within the border of the contrast enhancing part on T1-weighted images of the glioblastoma and a reference VOI was placed in the non-affected contralateral white matter. Automated segmentation and quantification of vessels within the two VOIs was achieved using multiscale vessel enhancement filtering in ImageJ. Results: Tumor vessels were clearly visible in all patients. When comparing tumor and the reference VOI, total vessel surface (45.3¡13.9 mm2 vs. 29.0¡21.0 mm2 (p,0.035)) and number of branches (3.5¡1.8 vs. 1.0¡0.6 (p,0.001) per cubic centimeter were significantly higher, while mean vessel branch length was significantly lower (3.8¡1.5 mm vs 7.2¡2.8 mm (p,0.001)) in the tumor. Discussion: ToF angiography at 7-Tesla MRI enables characterization and quantification of the internal vascular morphology of glioblastoma and may be used for the evaluation of therapy response within future studies.